INTEGRATION OF ARCHITECTURAL AND STRUCTURAL ASPECTS THROUGH THE DESIGN PROCESS: INDIVIDUAL RESIDENTIAL BUILDING - Dimitar Papasterevski, Toni Arangjelovski (My University, 2020)
Louis Sullivan's aesthetic credo "form follows function", has become fundamental to the modernist architectural movement. From today's point of view, the relations between form and function have changed so that sometimes structure can follow form, which at the same time implies the established of a new fundamental principle that would sound like "structure ever follows form". The paper tends to develop a framework for integrating architectural and structural design in order to achieve a harmonious coexistence between architectural technology and arts. Traditionally, through the process of developing the architectural idea in the preliminary design phase, architects are more concerned with form, composition, function and aesthetics; however, the structural properties of the distribution of the load-bearing elements are not taken into consideration at this stage. Our collaborative experience as an architect and civil engineer suggests a new approach to developing architectural projects by integrating the structural layout of elements at the earliest stage in conceptual design development. Through an example of our author project of a realised individual residential building, we will illustrate the exploration of these aspects. The load-bearing structure is a reinforced concrete skeletal system that defines space that we can call "generic space". The frame itself is specific and has qualities that determine the architecture for a long time. Finally, we proposed a framework for achieving a successful integration to evolve an architecturally pleasing and structurally efficient building. Architecture, as a successful creative product, can only be delivered within this process developed through the balance and harmony of all elements and actors as a whole.
Keywords: integration, frame, structural, generic space